Womenpreneur: Digital Marketing Perspective and the Ethical Dilemma on the Overclaim Phenomenon - Nurlinda Nurlinda; Nur Aisyah; Nurul Fakhriarni As’ary (SENTRALISASI, 2026)
The widespread phenomenon of overclaiming in marketing strategies influences customer purchasing decisions. This study will examine two perspectives: the factors influencing purchasing decisions from the customer perspective and the impact of overclaiming on the income of female entrepreneurs. This study uses two research approaches: a field experiment and an event study. The experimental method will be used to examine the determinants of customer purchasing decisions. Meanwhile, the event study will be used to examine the increase in business capacity in the face of the overclaiming phenomenon experienced by sellers. The research subjects were female skincare product consumers and three skincare brands experiencing overclaiming. Data analysis used path analysis and paired sample t-tests. This study shows that electronic word of mouth can influence purchasing decisions directly and indirectly. However, this does not apply to social media marketing, which requires the mediation of impulsive behavior. Other results also indicate that sellers' overclaiming strategies have a negative impact on sales revenue.